2005
DOI: 10.1021/bi050961w
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting the Roles of a Strictly Conserved Tyrosine in Substrate Recognition and Catalysis by Pseudouridine 55 Synthase

Abstract: Sequence alignment of the TruA, TruB, RsuA, and RluA families of pseudouridine synthases (PsiS) identifies a strictly conserved aspartic acid, which has been shown to be the critical nucleophile for the PsiS-catalyzed formation of pseudouridine (Psi). However, superposition of the representative structures from these four families of enzymes identifies two additional amino acids, a lysine or an arginine (K/R) and a tyrosine (Y), from a K/RxY motif that are structurally conserved in the active site. We have cre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
49
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(51 citation statements)
references
References 26 publications
0
49
1
Order By: Relevance
“…The same is true for mutations at other positions (Y173 and R267) in hPus1p; some mutations result in no activity, such as Y173S, but others show some activity toward modification at position 27 in the S. cerevisiae pre-tRNA Ile . When the corresponding tyrosine in E. coli TruB (Y67) was mutated to phenylalanine, leucine, or alanine, there was no detectable activity on a natural tRNA substrate (Phannachet et al 2005), suggesting that there was a need for both a hydrophobic ring and an OH group combined in one side chain (Phannachet et al 2005). These data would suggest that the functions of these highly conserved amino acids are less constrained in hPus1p than for instance R62 in RluA, R58 in TruA, and Y67 in TruB.…”
Section: Comparison Of Trua and Pus1pmentioning
confidence: 98%
See 1 more Smart Citation
“…The same is true for mutations at other positions (Y173 and R267) in hPus1p; some mutations result in no activity, such as Y173S, but others show some activity toward modification at position 27 in the S. cerevisiae pre-tRNA Ile . When the corresponding tyrosine in E. coli TruB (Y67) was mutated to phenylalanine, leucine, or alanine, there was no detectable activity on a natural tRNA substrate (Phannachet et al 2005), suggesting that there was a need for both a hydrophobic ring and an OH group combined in one side chain (Phannachet et al 2005). These data would suggest that the functions of these highly conserved amino acids are less constrained in hPus1p than for instance R62 in RluA, R58 in TruA, and Y67 in TruB.…”
Section: Comparison Of Trua and Pus1pmentioning
confidence: 98%
“…Analysis of the TruA crystal structure in addition to structural studies of members of other C families has suggested that the two arginines (R58 and R205 in TruA) play a role in constraining the aspartate and in flipping out the uracil base of the substrate allowing it to be modified (Foster et al 2000;Hamma and Ferré-D'Amaré 2006;Hur et al 2006;Hur and Stroud 2007). The role of the tyrosine at 118 in TruA has not been fully elucidated; however, a previous mutation study using TruB C synthase has shown that replacement of the tyrosine with alanine, phenylalanine, or leucine results in the lack of enzymatic activity on a natural substrate (Phannachet et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…1B; Nurse et al 1995). TruB was the first pseudouridine synthase to be crystallized in complex with its substrate RNA (Hoang and Ferré-D'Amaré 2001), and numerous biochemical investigations have been performed to investigate its substrate specificity and catalytic mechanism Hamilton et al 2005;Hoang et al 2005;Phannachet et al 2005). Furthermore, TruB is of general interest as it is a close homolog and structurally very similar to the eukaryotic pseudouridine synthase Cbf5, the catalytic subunit of H/ACA small nucleolar ribonucleoproteins (Koonin 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Pus10 does not contain this His. A Tyr residue in TruB that corresponds to Tyr339 of MjPus10, when mutated to Ala, Leu, or Phe, lost all of its Ψ55 synthase activity (Phannachet et al 2005). It has been proposed that this Tyr in TruB maintains the hydrophobic nature of the active site and its OH group is involved in catalysis (Phannachet et al 2005).…”
Section: Archaeal Pus10 Protein-trna Interaction: Plausible Mechanismmentioning
confidence: 99%
“…A Tyr residue in TruB that corresponds to Tyr339 of MjPus10, when mutated to Ala, Leu, or Phe, lost all of its Ψ55 synthase activity (Phannachet et al 2005). It has been proposed that this Tyr in TruB maintains the hydrophobic nature of the active site and its OH group is involved in catalysis (Phannachet et al 2005). Mutations of the corresponding Tyr in human PUS1 (member of TruA family) also show significant reduction of activity (Sibert et al 2008).…”
Section: Archaeal Pus10 Protein-trna Interaction: Plausible Mechanismmentioning
confidence: 99%